Cytokine profiles in patients with Q fever fatigue syndrome. Issue 5 (May 2019) - Raijmakers, Ruud P.H.; Koeken, Valerie A.C.M.; Jansen, Anne F.M.; Keijmel, Stephan P.; Roerink, Megan E.; Joosten, Leo A.B.; Netea, Mihai G.; van der Meer, Jos W.M.; Bleeker-Rovers, Chantal P.
Summary: Background: Q fever fatigue syndrome (QFS) is a state of prolonged fatigue following around 20% of acute Q fever cases. It is thought that chronic inflammation plays a role in its etiology. To test this hypothesis we measured circulating cytokines and the ex - vivo cytokine production in patients with QFS and compared with various control groups. Materials/methods: Peripheral blood mononuclear cells (PBMCs), whole blood, and serum were collected from 20 QFS patients, 19 chronic fatigue syndrome (CFS) patients, 19 Q fever seropositive controls, and 25 age- and sex-matched healthy controls. Coxiella -specific ex-vivo production of tumor necrosis factor (TNF)α, interleukin (IL)-1β, IL-6, and interferon (IFN) was measured, together with a total of 92 circulating inflammatory proteins. Results: PBMCs of QFS patients produced more IL-6 (P = 0.0001), TNFα (P = 0.0002), and IL-1β (P = 0.0005) than the various control groups when stimulated with Coxiella antigen. QFS patients had distinct differences in circulating inflammatory markers compared to the other groups, including higher concentrations of circulating IL-6 and IFNγ. Conclusion: QFS patients showed signs of chronic inflammation compared to asymptomatic Q fever seropositive controls, CFS patients, and healthy controls, of which the monocyte-derived cytokines TNFα, IL-1β, and especially IL-6, are likely crucial components.